Athena speciality certificate examination case for photodermatology. (1st July 2022) - Dubash, Faisal; Ibbotson, Sally
Abstract: This Athena case describes a young girl with a 2‐year history of episodic pruritic erythematous papules on her right cheek, which coalesced to form a plaque. The eruption later recurred, involving the left cheek, nose and upper arms.